High growth and gazelles enterprises in Portugal: a firm demography and growth analysis - Sarmento, Elsa (2014)
This paper describes employer enterprise dynamics in Portugal for High Growth and Gazelle enterprises for the period 1990‐ 2007 and discusses the main stylized facts related to these firms´ performance, longevity and employment by size, region and sector. Two parallel perspectives are provided, by turnover and by employment. The analysis carried out is based on a comprehensive dataset which provides the platform for uncovering features of Portuguese firms which have not been examined to such a detail before. In doing so, this study reveals potential business areas of growth which are of prime importance for a country’s economic growth and development.In addition, the paper also provides an international comparison between Portuguese firms and those in the UK. This comparison enables us to explore differences in national framework conditions and conclude that the regulatory environment in which Portuguese firms operate seem to be instrumental to the explanation of their poor performance relative to their UK counterparts.